Evaluation of pain assessment and management in critically Ill intubated patients in a referral university hospital in Iran - Babak Alikiaie; Sarah Mousavi; Ali Ebrahimi; Zahra Foroughi (Wolters Kluwer Medknow Publications, 2019)
Objective: This study aims to evaluate current pain assessment and management in critically ill patients and to describe (1) pain management episode, according to the behavioral pain scale (BPS), and (2) the effectiveness of analgesics, according to the recommendation of guidelines. Methods: In this cross-sectional study, a sample of 60 intubated critically ill patients was selected from the intensive care units (ICUs). A researcher evaluated the patient' pain severity using the BPS tool in patients receiving analgesics according to nurses' note. At each time of analgesic administration, the BPS score was recorded, and this process was repeated 72 h later. The appropriateness of pharmacological interventions was assessed according to the American College of Critical Care Medicine guideline. Findings: The most prescribed analgesic was morphine sulfate (48.3%) followed by fentanyl (23.3%). 55% of analgesics on day 1 and 25% on day 3 were prescribed appropriately according to the guideline recommendation and BPS score. Morphine was the most effective drug (17 patients out of 29). Even though a BPS score was <5, 26 patients received analgesics. Conclusion: Quality of pain assessment and management in our setting is inappropriate and inadequate, which leads to over- or under-use of analgesics. The lack of an established pain protocol may contribute to this situation.